Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Pencucian Uang Pasif - Talaohu, Abdussalam Ramdani; Sopacua, Margie Gladies; Leasa, Elias Zadrach (MATAKAO Corruption Law Review, 2023)
Introduction: Article 5 paragraph (1) of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. In this article, the maximum penalty is 5 years and a maximum fine of Rp. 1,000,000,000 (one billion rupiah). However, in the case of Faradibah Jusuf and his colleagues, one of the defendants on behalf of Soraya Pelu committed the crime of passive money laundering but was sentenced to 15 years in prison and a fine of five hundred million rupiah. This criminal provision exceeds the maximum criminal provisions in Article 5 paragraph (1). In addition, in this case there are 2 other suspected perpetrators, namely the initials DN and AMT, the closest people to the perpetrator Faradiba Yusuf, who is suspected of committing a passive money laundering crime, not being prosecuted and sentenced according to Article 5 paragraph (1) of Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. Purposes of the Research: This study aims to examine: Criminal liability against perpetrators of passive money laundering and the system of evidence for passive money laundering. Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field. Results of the Research: Criminal responsibility for the crime of money laundering can be imposed on criminals who receive funds or assets from the criminal subject to which criminal liability is required. There is a dissenting opinion from Judge Member 1 on Decision Number 5/Pid.Sud-TPK/2020/PN Amb, which basically explains that Judge Member 1 differs in opinion because according to Judge Member 1, the punishment for each of them must refer to the guidelines that have been set, issued by the Supreme Court of the Republic of Indonesia as contained in Supreme Court Regulation (Perma) Number 1 of 2020 dated 27 July 2020. This difference of opinion concerns the roles of each which are not the same as each other, causing unequal punishment.